Crystallization kinetics of thermoplastic elastomeric blends based on ground tyre rubber - Lima, Paulo S.
This work analyzes the crystallization process of thermoplastic elastomeric blends (TPE) based on ground tyre rubber (GTR). More specifically it analyzes the effect of GTR and fresh rubber materials, like ethylene propylene diene monomer (EPDM) and ethylene propylene rubber (EPR), on the crystallization of binary and ternary polypropylene (PP)-based blends. The crystallization kinetics is studied under isothermal and nonisothermal conditions using differential scanning calorimetry (DSC). The kinetic parameters derived from the Avrami model are used to study the effect of temperature and rubber materials on the nucleation mechanism, the morphology of the crystalline structures, and the crystallization rate. Results reveal that GTR has a strong nucleating effect on PP and that its presence leads to higher crystallization rates. The EPDM presence has a slight effect on the PP crystallization process whereas EPR has no significant effect. From the DSC curves it is possible to detect an inverse relationship between temperature and the crystallization rate. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42589.